Generalized stochastic derivatives on spaces of nonregular generalized functions of Meixner white noise - Kachanovsky, N.A. (Український математичний журнал, 2008)
We introduce and study generalized stochastic derivatives on the Kondratiev-type spaces of nonregular
generalized functions of Meixner white noise. Properties of these derivatives are quite analogous to the
properties of the stochastic derivatives in the Gaussian analysis. As an example we calculate the
generalized stochastic derivative of the solution of some stochastic equation with a Wick-type
nonlinearity. Вводяться та вивчаються узагальнені стохастичні похідні на пов'язаних із білим шумом Майкснера просторах типу Кондратьєва нерегулярних узагальнених функцій. Властивості цих похідних аналогічні властивостям стохастичних похідних у гауссівському аналізі. Як приклад обчислено узагальнену стохастичну похідну розв'язку певного стохастичного рівняння з нелінійністю типу Віка.